(untitled) (Revista de Artes Marciales Asiáticas, 2026)
This article aims to understand the construction of signs and sociocultural dispositions arising from the relationships established within a karate group in the Western Cariri region of the state of Ceará, Brazil. More specifically, it seeks to present the dissonances and affirmations surrounding the idea of a warrior ethos. Guided by the ethnographic method, the research involved participant observation and field diary entries from June 2023 to May 2024. Ten men and four women took part in the study. The researcher responsible for field immersion participated in karate training sessions and competitions, in addition to establishing a closer relationship with the investigated group, in order to position himself as an “insider.” Distinct forms of appropriation, interpretation, and decoding of karate signs were observed, in which the ethos of this practice operates in peculiar ways, ranging from an individual to a collective conception. Thus, the negotiation of this ethos occurs within a configurational field of tension, where hierarchical positions, personal trajectories, and the regional cultural context filter and reshape martial codes.